Critical-Size Bone Defects: Is There a Consensus for Diagnosis and Treatment?. (March 2018) - Nauth, Aaron; Schemitsch, Emil; Norris, Brent; Nollin, Zachary; Watson, J. Tracy
Abstract : Summary: There is a significant burden of disease associated with bone defects, and their management is challenging. These injuries have a profound clinical and economic impact, and outcomes are limited by high rates of complication and reoperation, as well as poor functional outcomes. There remains a lack of consensus around definitions, reliable models, and best practices for the surgical management of bone defects. The current state of the literature on bone defects is reviewed here, with a focus on defining critical-size bone defect, the use of the induced membrane technique, the role of biologics, and the management of infected bone defects. Abstract : Supplemental Digital Content is Available in the Text.